2010
DOI: 10.1093/eurheartj/ehq372
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary syndrome in human immunodeficiency virus-infected patients: characteristics and 1 year prognosis

Abstract: These results suggest that the acute management of ACS in HIV-infected patients can routinely be the same as that of HIV-uninfected patients, but that specific secondary prevention measures are needed to alleviate the increased risk of recurrent ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
95
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 25 publications
8
95
2
6
Order By: Relevance
“…2 The proportions of dyslipidemic patients in the 2 groups in the present study were similar to those in the study by Hsue et al, 13 but the present study was unable to differentiate between hypercholesterolemia and hypertriglyceridemia. Nevertheless, Boccara et al 12 and Hsue et al 13 showed a higher frequency of hypertriglyceridemia in infected patients but similar cholesterol levels. In the present study, the percentage of STEMI was 90% in HIV-infected patients, and previous studies have reported similar rates.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…2 The proportions of dyslipidemic patients in the 2 groups in the present study were similar to those in the study by Hsue et al, 13 but the present study was unable to differentiate between hypercholesterolemia and hypertriglyceridemia. Nevertheless, Boccara et al 12 and Hsue et al 13 showed a higher frequency of hypertriglyceridemia in infected patients but similar cholesterol levels. In the present study, the percentage of STEMI was 90% in HIV-infected patients, and previous studies have reported similar rates.…”
Section: Discussionmentioning
confidence: 93%
“…[11][12][13][14][15]17 However, only 4 of those studies included a control group of uninfected patients, [12][13][14]17 and only 2 of the studies 12,14 matched the 2 groups for age, sex, and type of MI. In the present study, the prevalence of diabetes mellitus and hypertension was lower in HIV patients than in non-HIVinfected patients, and these results are in agreement with 2 other studies by Boccara et al 12 and Hsue et al, 13 who found similar values (20% and 10%, respectively). With regard to comorbidities, atrial fibrillation was less common among HIVinfected patients, probably because of their age and the lower prevalence of hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations